(untitled) (Research, Society and Development, 2020)
In Brazil, the portion of the population that has some type of limitation or disability is almost always excluded from urban planning, with the guarantee of their right to the city being restricted. In the city of Salvador, capital of Bahia, the contrast between public and private places denounces the differentiation in investments, in inspections and in the applicability of regulations for adapting spaces for people with disabilities and reduced mobility. In view of the affirmative, having citizenship as a subject of study in terms of accessibility, the general objective of the research is to analyze accessibility to the beaches of Salvador, a public leisure option, relating it to urban transport modes and the edge requalification. To achieve this objective, qualitative research was sought, based on concepts relevant to the proposed theme, and field research with visits to beaches in order to observe accessible aspects. The work considers the norms and statutes of adequacy and accessibility, also highlighting social recreation projects that promote more humanized access to beaches, such as ParaPraia and Praia Eficiente, initiatives in force in the city. The study demonstrates that the bahian capital, in the recent period, has been adopting policies that seek the construction of an inclusive urban architecture and a more conscious society.